P-OGC27 Chyle Leak following Oesophagectomy: 'A Retrospective 10-year Single-Site Experience of a Tertiary Centre.'. (16th December 2021) - Koroma, Paul; Chaudhury, Madhu; Greenlees, Alana; Ball, Christopher; Shetty, Vinutha; Turner, Paul; Ward, Jeremy; Pursnani, Kishore
Abstract: Background: Chyle leak is a relatively uncommon but well-recognised complication following Oesophagectomy which carries significant morbidity and mortality if not treated actively. Evidence suggests the incidence rate of chyle leak post oesophagectomy can range from 0.4% to 21%. The aim of this study was to describe our experience in managing this complication. Methods: This was a retrospective study, using the electronic database, to analyse our incidence of chyle leak in all patients who underwent elective oesophagectomy from April 2009 to December 2019 in a Tertiary Upper GI cancer centre. The diagnosis was confirmed by high persistent chest drain output, the colour of the fluid produced in the chest drain and its 'content' including fluid triglyceride levels and the presence of chylomicrons. Results: Between 2009-2019, a total of 550 patients underwent Oesophagectomy. The median length of stay was 13 (Range 3 to 148) days. The median age was 63 years (45 to 82) with M:F 2:1. Chyle leak was identified in 24 patients (4.4%); Patients who were managed surgically were 83.3%(n = 20) with a median LOS of 20 days (Range 11 to 148) and mortality of 5%(n = 1). 16.7%(n = 4) were managed conservatively with a median LOS of 31 days (Range 14 to 51) and mortality of 0%.  All 24 patients with chyle leak had neoadjuvant chemotherapy as part of treatment with radical intent.  Conclusions: Low mortality rates with chyle leak can be achieved with a high index of suspicion and early surgical intervention. This is crucial in reducing the length of stay in hospital and morbidity. Conservative management is suitable in low volume chyle leak and cases clinically responding to medical management.